Determination of Consumer Decisions in Re-Choosing Prames Catering Services: The Role of Product Quality, Price Perception & Customer Satisfaction - Muhammad Rusdi Ridjal; Sufrin Hannan; Agus Setyo Pranowo (PT. INOVASI TEKNOLOGI KOMPUTER, 2026)
The increasingly competitive catering service industry demands that companies retain customers to continue using their services. This study aims to analyze the influence of product quality and price perception on the decision to repurchase Catering Prames services, with customer satisfaction as an intervening variable. The research uses a quantitative approach thru a survey method targeting Catering Prames customers in 2024, selected using purposive sampling technique. Data were collected thru a Likert scale questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The research results show that product quality and price perception have a positive and significant impact on customer satisfaction and repurchase intention. Customer satisfaction also has a positive effect on the decision to repurchase and has been proven to mediate the influence of product quality and price perception. These findings indicate that product quality consistency, pricing aligned with perceived customer value, and enhanced satisfaction are important strategies to encourage repeat purchase decisions and strengthen the competitiveness of Catering Prames